Effect of HNO3 Concentration on Etch Rate and Structure of Si Wafer Etched in the Mixture of HF and HNO3 Solutions - F. Nurhaziqah K; C. K. Sheng; K. A. M. Amin; M. I. N. Isa; M. F. Hassan; E. A. G. E. Ali; K. H. Kamarudin; R. Aarif (Akademi Sains Malaysia, 2024)
The new microelectronic products require the silicon (Si) wafer to be thinned to less than 150 m in thickness. Residual defect on the wafer surface that leads to wafer breakage with a rough surface still be produced by mechanical grinding. Thus, chemical etching method is essentially applied to produce a reliable thin wafer with smooth surface of desired thickness. In this work, we studied the wet chemical etching effect of different HNO3 concentrations on total thickness and weight loss, etch rate, morphological and structural properties of Si wafer in the mixtures of HNO3 and HF. The results showed that the total thickness and weight loss increases with the increasing of HNO3 concentration and etching time. Higher HNO3 concentration causes higher etch rate, and the etch rate decreases at prolonged etching time. A smoother and clearer homogeneous Si surface image was observed by optical microscope as the etching time and HNO3 concentration increase. XRD analysis shows that the intensity of etched Si wafer is higher than the pure one, which might indicate the smoother surface formation after etching. The findings of present study can be valuably referred to produce a reliable and desired Si thin wafer which is crucial in integrated circuit fabrication.